REINFORCING ALTERNATIVE ASSESSMENT TO PROMOTE AUTHENTIC ASSESSMENT IN ENGLISH YOUNG LEARNERS’ CLASSROOM - Metty Agustine Primary (The Journal of English Literacy Education: The Teaching and Learning of English as a Foreign Language, 2015)
Abstract: This paper discusses the process of alternative assessment in English young learners‟ classroom. As regard with the assessment, it is a process which cannot be separated from the process of teaching learning. It is a fact that in Indonesia teacher usually assesses learners by focusing on summative test – also called as traditional test- a test for assessing learners after they accomplish the course. This also happens to English young learners‟ classroom. Young learners should be encouraged also to do formative assessment to see not only the result, but also the process of learning English. Alternative assessment consists of a method of finding out what a student knows or can do; it is intended to show growth and inform instruction, and it is an alternative to traditional forms of testing, namely multiple-choice tests . This paper describes some theories (library research) which underpin the assessment as integral part of teaching; it also presents the kinds of alternative assessment that can be utilized by teacher in the teaching learning process to promote authentic assessment for young learners .Key words: alternative assessment, authentic assessment, English young learners’ classroom